Novalis and Mathematics A Study of Friedrich von Hardenberg's Fragments on Mathematics and its Relation to Magic, Music, Religion, Philosophy, Language, and Literature - Dyck, Martin (UNC Studies in the Germanic Languages and Literatures, 1960)
A study of in the interrelationship of the sciences and the humanities grounded in the writings of Novalis in the early Romantic period, this work is of special interest to literary historians, mathematicians, and mathematical historians. Alongside his analysis of Novalis' fragments relating to mathematics Dyck gives commentary on previous scholarship and a history of mathematics in the eighteenth century as both science and philosophy.